Review of the fish genus Epinnula Poey (Perciformes: Gempylidae), with description of a new species from the Pacific Ocean - Ho, Hsuan-Ching; Motomura, Hiroyuki; Hata, Harutaka; Jiang, Wei-Chuan (Zootaxa, 2017)
The gempylid fish genus Epinnula is reviewed and two species are recognized. The type species E. magistralis is considered restricted to the western Atlantic Ocean and a new species from the Pacific Ocean is described. The new species, Epinnula pacifica sp. nov., can be distinguished from E. magistralis by 17 or 18 dorsal-fin rays (vs. 15 or 16 in E. magistralis), 15 or 16 anal-fin rays (vs. 13 or 14), 247–268 total scales on lower lateral line (vs. 285–330), a deeper body, relatively high dorsal fin as reflected by the relatively long fin spines and rays, longer dorsal-fin and anal-fin bases, longer pectoral fin, and longer pelvic fin and pelvic spine.